A systematic review of venous thromboembolism prophylaxis strategies in patients with renal insufficiency, obesity, or on antiplatelet agents. Issue 7 (12th June 2013) - Kebede, Sosena; Prakasa, Kalpana R.; Shermock, Kenneth; Shihab, Hasan M.; Brotman, Daniel J.; Sharma, Ritu; Chelladurai, Yohalakshmi; Haut, Elliott R.; Singh, Sonal; Segal, Jodi B.
Abstract : BACKGROUND: There is uncertainty about optimal strategies for venous thromboembolism (VTE) prophylaxis among select populations such as patients with renal insufficiency, obesity, or patients taking antiplatelet drugs including aspirin. Their physiologies make prophylaxis particularly challenging. PURPOSE: We performed a comparative effectiveness review of the literature on efficacy and safety of VTE prophylaxis in these populations. DATA SOURCES: We searched MEDLINE, EMBASE, SCOPUS, CINAHL, International Pharmaceutical Abstracts, clinicaltrial.gov, and the Cochrane Library through August 2012. Eligible studies included controlled trials and observational studies. DATA EXTRACTION: Two reviewers evaluated studies for eligibility, serially abstracted data, and independently evaluated the risk of bias and strength of evidence supporting interventions to prevent VTE in these populations. RESULTS: After a review of 30, 902 citations, we identified 9 controlled studies, 5 of which were trials, and the other 4 were observational studies. Five articles addressed prophylaxis of patients with renal insufficiency, 2 addressed obese patients, and 2 addressed patients on antiplatelet agents. No study tested prophylaxis in underweight patients or those with liver disease. The majority of observational studies had a high risk of bias. The strength of evidence ranged from low to insufficient regarding the comparative effectiveness and safety of VTE prophylaxis among these patients. CONCLUSION: The current evidence is insufficient regarding optimal VTE prophylaxis for patients with renal insufficiency, obesity, or those who are on antiplatelet drugs including aspirin. High‐quality studies are needed to inform clinicians about the best VTE prophylaxis for these patients. Journal of Hospital Medicine 2013;8:394–401. © 2013 Society of Hospital Medicine